Development of in-vitro and in-vivo bioassays to elucidate the mechanism of action of a synthetic novel compound N-phenethyl-pentan-3-amine (FK70) - Govindaraju, Kayatri (2020)
Hypertension, while being the most common condition of the circulatory system, it has been the greatest attributor to the burden of cardiovascular diseases. Despite the availability of a broad-spectrum pharmacological and non-pharmacological means to control blood pressure, the average blood pressure values over the past decades have remained unchanged. Moreover, in some countries, the trend has been increasing. Such occurrence precipitates a real demand for the discovery and development of newer drugs to treat this condition. In an earlier project, Schwarzinicine A (Sch A), a phenylethylamine alkaloid, was isolated from the leaves of Ficus Schwarzii. Sch A was shown to have similar vasorelaxation effect as dobutamine and isoprenaline (β-adrenoceptor agonists), and verapamil (a calcium channel blocker) in the rat aorta. Sch A, as compared with these molecules, was more effective in its ability to relax the blood vessel. N-phenethyl-1-phenyl-pentan-3-amine, (FK70) is a novel compound synthesized based on the main pharmacophore of Sch A as an alternative compound to study the mechanism of action of the novel compound. The primary goal of this study was to elucidate the mechanism of action of FK70 as a vasorelaxant. Initially, the primary pharmacological effects of FK70 were examined on different biological systems using rat isolated smooth muscle tissues (aorta, trachea, and bladder), porcine coronary artery (PCA), and guinea pig ileum. FK70 exhibited relaxation effect in all the tissue types tested, with the higher relaxation effect in the vascular smooth muscle tissues. Subsequently, an evaluation of the pharmacological actions of FK70 in rat aorta were performed. The effects of FK70 were tested in the presence of endothelium and nitric oxide (NO), alpha- and beta-adrenoceptors, potassium channels, and calcium channels. The findings showed that the aortic relaxation by FK70 was not affected by all modulators as mentioned earlier, except it inhibited extracellular calcium entry as suggested from the reduced contraction responses of potassium chloride (KCl) and G-protein coupled receptors (GPCR) linked contractile agents as well as the contractions by calcium chloride in calcium-free Krebs solution. Next, the role of extracellular and stored calcium (Ca2+) in contractile agents mediated responses were examined in rat aorta. The findings showed that (1) the role of stored and extracellular Ca2+ in Gq-protein activation (PE and 5-HT) are not the same and (2) the contractile agents (PE, 5-HT, and KCl) depends mostly on extracellular Ca2+ to cause a contraction in the rat aorta. To demonstrate the role of Ca2+ on FK70 effect, FK70 was tested with known calcium channel blockers, nifedipine (an L-type Ca2+ channel blocker) and SKF 96365 (a non-selective TRPC blocker) in normotensive rats (SD) and spontaneously hypertensive rats (SHR). The study exhibited that the relaxation effect of FK70 is comparable to that of known calcium channel blocker, SKF 96365 and the most important mechanism that seemed to be involved in FK70-induced relaxation is inhibition of extracellular Ca2+ influx in both SD and SHR. Finally, the effects of FK70 was examined in-vivo using Caenorhabditis elegans (C. elegans). The study allowed the assessment of both calcium inhibiting property and toxicity effect of FK70. The evaluation of pharyngeal pumping further confirmed the calcium blocking property of FK70 and prolonged exposure to FK70 did not induce a toxic effect on the lifespan of C. elegans. Taken together, FK70 exhibited an inhibitory role on calcium -dependent contraction in all the animal models tested. Hence the potential of developing FK70 as an alternative treatment for resistance hypertensive is promising.